2019
DOI: 10.3389/fmicb.2019.02077
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal, Plant Growth-Promoting, and Genomic Properties of an Endophytic Actinobacterium Streptomyces sp. NEAU-S7GS2

Abstract: Diseases caused by Sclerotinia sclerotiorum have caused severe losses of many economically important crops worldwide. Due to the long-term persistence of sclerotia in soil and the production of air-borne ascospores, synthetic fungicides play limited roles in controlling the diseases. The application of antagonistic microorganisms can effectively reduce the number of sclerotia and eventually eradicate S. sclerotiorum from soil, and therefore considerable interest has been focused on biological control. Streptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 75 publications
1
39
0
Order By: Relevance
“…Hence, the utilization of beneficial microorganisms as biological control agents is considered an environmental friendly alternative to combat crop diseases and pesticide resistance. Among microorganisms, actinobacteria especially Streptomyces are recognized for their ability to generate various active compounds with agricultural applications (Liu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the utilization of beneficial microorganisms as biological control agents is considered an environmental friendly alternative to combat crop diseases and pesticide resistance. Among microorganisms, actinobacteria especially Streptomyces are recognized for their ability to generate various active compounds with agricultural applications (Liu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on actinobacterial genome revealed genes related to plant growth promoting activities primarily production of IAA, siderophore, phosphate solubilization, and phytopathogen inhibition ( Gupta et al, 2014 ; Liu et al, 2019 ; Nouioui et al, 2019a ). Predictive genes obtained from genome mining in this study supported the experimental data on IAA and siderophore producing abilities of M. chalcea CMU55-4 in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…are Gram-positive filamentous bacteria ubiquitous in the soil as free-living organisms and symbionts of plants and animals (Seipke et al 2012). They are renowned for producing a wide variety of biologically active secondary metabolites, and therefore, there are increasing attempts to apply them in agriculture as plant growth promoters or biological control agents (BCA) (Xiao et al 2002;Bonaldi et al 2014;Colombo et al 2019b, a;Liu et al 2019). While until 2010, less than 10 reports were published yearly with the keywords 'Streptomyces' and 'biocontrol', in the last 10 years, 50-80 scientific papers have been published each year (www.…”
Section: Introductionmentioning
confidence: 99%